English Department Students' Perception on Teaching Assistance Program at Universitas Negeri Padang - Lidya Nitami; Havid Ardi (Universitas Negeri Padang, 2023)
The teaching assistance program is one of the courses the faculty offers to help students become ready to become professional teachers. This teaching assistance is carried out by a different program, created by Mr. Nadiem Makariem as the Minister of Education in the Emancipated Learning (MBKM), and teaching assistance organized by Universitas Negeri Padang. This study will discuss the students’ perception on teaching assistance program organized by Minister of Education and Culture and teaching assistance program organized by Universitas Negeri Padang. This research uses descriptive research with a random sampling technique involving 15 students who participated in teaching assistance program organized by Minister of Education and Culture and 16 students who participated in teaching assistance program organized by UNP. The research setting is English Education Study Program, Universitas Negeri Padang. Research results were collected through a questionnaire where statements were developed based on (Shinkfield & Stufflebeam, 1995) and an interview based on (Citraningtyas, 2021). The results of the study show that there is no significant difference in students’ perception between teaching assistance program organized by Minister of Education and Culture and teaching assistance program organized by UNP.